2005
DOI: 10.1111/j.1365-3180.2005.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed survival and predation of Anoda cristata in soyabean crops

Abstract: Anoda cristata is a troublesome annual broad-leaved weed in summer crops in the rolling Pampa in Argentina; seeds are the only source of regeneration of this species. Seed persistence or depletion is the result of survival and loss processes, including predation. The objective of this study was to determine survival at two burial depths in undisturbed soil and predation rates of A. cristata seeds in soyabean crops in different rotations and tillage systems. Survival was discontinuous and decreased to 25% after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…So far, contrasting effects have been reported with regard to the role of plant litter and mulches on seed predation rates (e.g. Reader, 1993; Brust, 1994; Puricelli et al. , 2005; Pullaro et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, contrasting effects have been reported with regard to the role of plant litter and mulches on seed predation rates (e.g. Reader, 1993; Brust, 1994; Puricelli et al. , 2005; Pullaro et al.…”
Section: Discussionmentioning
confidence: 99%
“…The soil surface is an extremely dangerous place for a seed because of the presence and activity of post‐dispersal seed predators. This danger diminishes when seeds are covered by soil or plant litter, because covered seeds are less likely to be consumed by seed predators than are exposed seeds (Thompson, 1987; Hulme, 1994; Hulme & Borelli, 1999; Puricelli et al. , 2005), although some predators will dig for buried seeds (Reichman, 1979; Abramsky, 1983;White et al.…”
Section: Introductionmentioning
confidence: 99%
“…Inversion operations bury weed seeds at a depth where the seeds are less prone to predation and germination (e.g. Puricelli et al. , 2005) and thus persist longer (Mohler & Galford, 1997; Omami et al.…”
Section: Resultsmentioning
confidence: 99%
“…In general, surface residue or vegetation has been shown to be an important factor promoting predation. For example, Puricelli et al (2005) suggested that the major factors influencing seed predation in zero-tillage wheat/soybean rotation were the higher crop residue levels which provided a favorable habitat for seed predators. Shelter is crucial for hiding from predators and affects predator behavioral decisions such as microhabitat choice, feeding activity, and movement (Lima and Dill, 1990).…”
Section: Promoting Predationmentioning
confidence: 99%